Hydrogen-induced transgranular to intergranular fracture transition in bi-crystalline nickel. (November 2021) - Ding, Yu; Yu, Haiyang; Zhao, Kai; Lin, Meichao; Xiao, Senbo; Ortiz, Michael; He, Jianying; Zhang, Zhiliang
Abstract: It is known that hydrogen can influence the dislocation plasticity and fracture mode transition of metallic materials, however, the nanoscale interaction mechanism between hydrogen and grain boundary largely remains illusive. By uniaxial straining of bi-crystalline Ni with a Σ5(210)[001] grain boundary, a transgranular to intergranular fracture transition facilitated by hydrogen is elucidated by atomistic modeling, and a specific hydrogen-controlled plasticity mechanism is revealed. Hydrogen is found to form a local atmosphere in the vicinity of grain boundary, which induces a local stress concentration and inhibits the subsequent stress relaxation at the grain boundary during deformation. It is this local stress concentration that promotes earlier dislocation emission, twinning evolution, and generation of more vacancies that facilitate nanovoiding. The nucleation and growth of nanovoids finally leads to intergranular fracture at the grain boundary, in contrast to the transgranular fracture of hydrogen-free sample. Graphical abstract: Image, graphical abstract